A mini exploration on the factors of personal bankruptcy among Malaysian's youth - Mohd Yusoff, Yuslizawati; Ismail, Norashikin; Hussain, Nor Azmawati (UiTM Cawangan Johor, 2024)
This paper exploring factors influencing the occurrence of personal bankruptcy among Malaysian youth. As this paper is a mini project, we only have two informants as part of our method in getting data in exploring the topic. Therefore, this study utilizes a very simple approach in exploring the topic about personal bankruptcy among youth in Malaysia. Several key factors being identified as the contributor to personal bankruptcy including socioeconomic background, educational attainment, employment status, financial literacy, and access to credit. Findings in this study also stressed the importance of financial education and its potential positive impact on individuals' financial wellbeing and bankruptcy prevention. Youth behaviour and attitude also being emphasizes in financial decision-making and bankruptcy outcomes, aligning with previous quantitative studies. With the findings from the informants, this study shall able to highlight the complex interplay of these factors in determining the likehood of personal bankruptcy among young Malaysians. It is very important to those individual youth to measure their readiness to accept or respect their values or practices at the debt level to avoid bankruptcy. This study provides valuable insights into the factors contributing to personal bankruptcy in Malaysia, emphasizing the critical role of financial management, lending practices, behaviour and attitude, and financial education. In a possible way, a policy implication has also been highlighted as the need for targeted interventions to enhance financial education, promote responsible lending practices, and support economic opportunities for youth. By addressing the factor, this study found that it is very crucial to mitigate the impact of personal bankruptcy and fostering financial resilience among Malaysian youth. By elucidating these dynamics, this study contributes to a deeper understanding of the multifaceted challenges faced by young Malaysians in managing personal finances and navigating the complexities of modern financial systems.